EKSISTENSI SAGU SEBAGAI KONSUMSI DARI PEWARISAN MASYARAKAT MELAYU DESA PANGGAK LAUT KABUPATEN LINGGA - Heri Syahputra Lingga; Nanik Rahmawati; Siti Arieta (LPPM STISIP Persada Bunda, 2023)
Sago one of the food sources with high carbohydrate content. Sago also has a very high cultural value as one of the local wisdom in traditional communities that has always been maintained for generations. The potential of sago is developed as a food substitute for rice, a factor that affects the existence of sago through science and technology sago is processed with various kinds of products with processing that attracts young people. The purpose of this research is to find out that sago still exists today with a variety of preparations made from sago-based ingredients. The foods that exist are ring crackers, bangkit cakes, lenggang sago chips, laksa, kepurun, sapwood, sago plates, lambok. In this study, researchers used qualitative methods by collecting data on observation, interviews, and documentation. Researchers used Distingsi theory (Pierre Bourdieu) which explains the recombination of cultural aspects, especially high culture, with an anthropological understanding of culture as a whole including its high and low aspects. In this context, it has a high taste value with food made from staple ingredients. The results of this research are food processed from sago dasr ingredients. It has a very high cultural value so that it still exists, besides that sago can also be processed into various types of food and has a unique taste, and is well known to the wider community.